Anti-TNF-alpha-induced lupus in patients with non-infectious uveitis. Issue 2 (March 2023) - Miguel-Escuder, Lucia; Garcia Tirado, Amanda; Sainz-de-la-Maza, María; Espinosa, Gerard; Moll-Udina, Aina; Llorenç, Víctor; Parrado-Carrillo, Alba; Adán, Alfredo
Purpose: Anti-TNF-α-induced lupus (ATIL) is a rare condition considered as a drug-induced lupus (DIL) in patients under anti-TNF-α therapies. Nowadays it is still unclear if ATIL is a classical DIL or represent a distinct syndrome. Some characteristics of DIL have been described specifically associated with patients with lupus-like syndrome receiving anti-TNF-α therapy: the severity of the disease, incidence/prevalence of dsDNA antibodies (anti-dsDNA) and hypocomplementaemia. The objective of this study is to describe the development of ATIL in patients with non-infectious uveitis in a single tertiary center. Methods: Retrospective description of a case series. Results: We describe three patients with noninfectious uveitis (NIU) of different etiologies who developed antinuclear antibody (ANA) and anti-dsDNA antibody positivity, arthritis and, in one case, skin lesions under adalimumab treatment. The condition resolved in all of them after adalimumab withdrawal. Corticosteroids were required in one patient, non-steroidal anti-inflammatory drugs in two patients, and hydroxychloroquine in one of them. None required another immunosuppressive drug. A subsequent control of the NIU could continue to be carried out without anti-TNF-α therapy in two patients and in the remaining a switch was made to another anti-TNF-α (golimumab). Conclusion: The current report describes three cases of ATIL in patients with different types of NIU which share some common features: ANA positivity, articular symptoms, and a temporal relationship between symptoms onset and anti-TNF-α treatment. A review of the literature and comparison with the few previous reported ATIL cases was conducted as well.